Meaningful Connections in Crisis: Exploring Motivational and Emotional Predictors of Online Prosocial Behavior Among Indonesian Youth - Malizall, Zelynda Zeinab; Rizqi, Putri Umrotur (Psychosocia : Journal of Applied Psychology and Social Psychology, 2024)
The global COVID 19 crisis catalyzed a surge in online prosocial behaviors among youth, particularly in collectivist cultures such as Indonesia. This study investigates the motivational and psychosocial determinants that drive Indonesian youths to engage in public versus anonymous digital altruism. Drawing on survey data from 500 respondents aged 15–25, we employed structural equation modeling to examine how eudaimonic, extrinsic, and hedonic motivations influence online prosocial behavior, with empathy and trust in social platforms as mediating factors. Using validated psychological scales, our cross sectional analysis reveals that eudaimonic motivation significantly predicts anonymous prosocial actions, while extrinsic motivation is a primary driver of public acts. Hedonic motivation was found to be a weak and inconsistent predictor. Empathy and trust play critical mediating roles, facilitating the translation of motivation into behavioral outcomes. The findings suggest that public behavior is often shaped by reputational goals, whereas anonymous actions are rooted in intrinsic meaning making and emotional resonance. Our results support the implementation of culturally tailored digital interventions, such as gamification and peer mentoring systems, which promote eudaimonic engagement while addressing trust and empathy building in virtual environments. Methodological considerations include the limitations of self report bias and the need for mixed method validation. Future research should examine platform specific influences and cross cultural comparisons to deepen the theoretical understanding of youth digital altruism. These insights contribute to a more nuanced understanding of digital prosociality and offer strategic guidance for educators, policymakers, and digital platform designers aiming to foster meaningful online civic participation.